FACEBOOK'S TWO DECADES: TRAVERSING THE SPECTRUM FROM VIRTUAL COMMUNALISM TO ALLEGED REALITY CENSORSHIP:LITERATURE REVIEW - Indah Sulistiani; Muhammad Yazidus Syukri; Syarifuddin; Sitti Nur Alam (Adisam Publisher, 2024)
This comprehensive literature review embarks on a nuanced odyssey through the multifaceted evolution of Facebook spanning two decades, transmuting from a bastion of virtual communalism to grappling with intricate allegations of reality censorship. The narrative unfurls by critically traversing key phases, unraveling the platform's embryonic role as a crucible for virtual community-building, and meticulously dissecting the labyrinthine shifts in user dynamics. The analysis intricately probes the elusive realm of alleged censorship practices, scrutinizing their rippling repercussions on a kaleidoscopic spectrum of perspectives. Furthermore, the review delves into the intricacies of privacy violations, peeling back the layers to unveil their far-reaching consequences and offering profound insights into the multidimensional challenges that have intricately sculpted Facebook's tumultuous journey. Like a scholarly artisan, the methodology meticulously dissects an extensive corpus of academic articles, presenting a sophisticated and exhaustive understanding of Facebook's intricate dance within the ever-evolving and enigmatic digital landscape.